Sex moderates the association between symptoms of anxiety, but not obsessive compulsive disorder, and error‐monitoring brain activity: A meta‐analytic review. (January 2016) - Moser, Jason S.; Moran, Tim P.; Kneip, Chelsea; Schroder, Hans S.; Larson, Michael J.
Abstract: Sex differences in cognition and emotion are particularly active areas of research. Much of this work, however, focuses on mean‐level differences between the sexes on cognitive and/or emotional variables in isolation. In this article, we are primarily concerned with how sex affects associations between cognition and emotion, or cognition‐emotion interactions. Specifically, the purpose of this paper is to shed light on a gap in our understanding of how sex affects the relationship between error monitoring, a core component of cognitive control, and anxiety. Using meta‐analysis, we show that the relationship between symptoms of anxiety and a neurophysiological marker of error monitoring—the error‐related negativity (ERN)—is significantly greater in women than men such that women, but not men, with higher levels of anxiety show a larger ERN. This sex difference held true across studies of anxiety‐specific symptoms but not studies of obsessive‐compulsive symptoms. These findings underscore the need to consider sex in studies of anxiety and the ERN as well as support growing evidence indicating that obsessive‐compulsive problems are distinguishable from other anxiety‐specific problems across multiple levels of analysis. Overall, we conclude that ignoring sex in studies of cognition‐emotion interactions is unacceptable. Rather, future research that continues to tackle questions related to sex differences in associations between cognition and emotion will more likely lead to advancements in basic and applied sciences of relevance to health and human behavior.